Knowledge graphs and semantic web: first Iberoamerican conference, KGSWC 2019, Villa Clara, Cuba, June 23-30, 2019, Proceedings - Villazón-Terrazas, Boris; Hidalgo Delgado, Yusniel (Communications in computer and information science, 2019)
A Model for Language Annotations on the Web -- A Description Logic for Unifying Different Points of View -- OceanGraph: Some Initial Steps Toward a Oceanographic Knowledge Graph -- Digital Repositories and Linked Data: Lessons Learned and Challenges -- Author-Topic Classication based on Semantic Knowledge -- A General Process for the Semantic Annotation and Enrichment of Electronic Program Guides -- Extraction of Semantic Web Statements from Text -- Meta-modelling Ontology Design Pattern -- Automated Large Geographic Ontologies Generation Method from Spatial Databases. -Towards the Semantic Enrichment of Existing Online 3D Building Geometry to Publish Linked Building Data -- A Method for Automatically Generating Schema Diagrams for Modular Ontologies.-Conformance Test Cases for the RDF Mapping Language (RML) -- Expressive Context Modeling with Description Logics. -Dimensions Affecting Representation Styles in Ontologies